Listeria monocytogenes Brain Abscess within a Metastatic Intracerebellar Space-Occupying Lesion in a Patient with Carcinoma Lung: First Case Report from India - Oommen, Arun; Johny, Molly; Pratap, Thara; Paul, Renu Suresh; Chinnan, Jily P.; Jalal, Muhammed Jasim Abdul (Indian Journal of Neurosurgery, 2017)
Listeria monocytogenes infections are rare. Neonates and geriatric population, pregnant women, and diabetic and immunocompromised patients are at higher risk for invasive listeriosis. Early recognition of Listeria brain abscess remains a major challenge. Here, we describe a case of intratumoral abscess with L. monocytogenes in a patient with intracerebellar metastasis from poorly differentiated adenocarcinoma lung. Right cerebellar tumor with a thick-walled purulent cavity was resected. Histopathologic examination revealed acute inflammation consistent with abscess and showed metastatic poorly differentiated adenocarcinoma. Cultures of the abscess fluid grew L. monocytogenes. She responded well to ampicillin-gentamycin therapy and the surveillance imaging done on the seventh postoperative day showed clearance of the abscess. The patient is further being planned for radiotherapy in regard to metastasis. Listeria abscess within a metastatic tumor is very rare and only one case is reported as of our knowledge. Listeria abscess being reported within an intracerebellar metastatic space-occupying lesion is for the first time.
Keywords: Listeria monocytogenes brain abscess; brain abscess within a metastasis; intracerebellar brain abscess